Clothing Thermal Resistance in the Human Biometeorological Models - Ács, Ferenc; Szalkai, Zsófia; Kristóf, Erzsébet; Zsákai, Annamária (Geographica Pannonica, 2023)
Three different clothing thermal resistance (rcl) schemes are compared using meteorological and human data collected in Martonvásár. Model 1 is the most complex, it is energy balance based and it can be used as stand‑alone human biometeorological model. Model 3 is the simplest, it is the UTCI‑clothing model used as sub‑model in the UTCI (Universal Thermal Climate Index) scheme. It uses air temperature as sole input. Model 2 uses more data than model 3, the data used are the thermal insulation values of the clothing worn. Meteorological data refer to the town Martonvásár. The data were collected in the period August 9, 2016 – May 23, 2018. The main result is that the rcl values obtained by model 1 differ significantly in most of the cases from the results obtained by models 3 or 2. The agreement of models 2 and 3 is acceptable. The fact that the results of model 1 rarely match the results of model 3 or model 2 suggests that the energy balance between human body and environment is rarely achieved, merely is this the case in approximately 10 percent of the cases. Further testing is required to be sure of the certainty of the obtained results.